2022
DOI: 10.21203/rs.3.rs-2038767/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kidney tubular epithelial cell ferroptosis links glomerular injury to tubulointerstitial pathology in lupus nephritis

Abstract: While the deposition of immune complexes in the glomeruli is thought to initiate lupus nephritis, the extent of tubular damage better predicts progression to end stage kidney disease than the glomerular injury. However, the mechanisms underlying tubular injury in lupus nephritis are incompletely understood. Iron accumulates in tubular epithelial cells of lupus nephritis patients and mice. Ferroptosis is a druggable, iron-dependent form of cell death that is characterized by lipid peroxidation but has received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Various research studies have highlighted the significance of Lip-1 in treating different neurological disorders and cancers. A recent study revealed that a Lip-1 analog, Lip-2, successfully prevented ferroptosis induced by serum in human proximal tubular epithelial cells from patients with lupus nephritis (Class IV), while also exhibiting improved pharmacokinetics (Alli et al, 2023).…”
Section: Exogenous Free Radical Trapping Antioxidantsmentioning
confidence: 99%
“…Various research studies have highlighted the significance of Lip-1 in treating different neurological disorders and cancers. A recent study revealed that a Lip-1 analog, Lip-2, successfully prevented ferroptosis induced by serum in human proximal tubular epithelial cells from patients with lupus nephritis (Class IV), while also exhibiting improved pharmacokinetics (Alli et al, 2023).…”
Section: Exogenous Free Radical Trapping Antioxidantsmentioning
confidence: 99%
“…Cystolic Fe 2+ catalyzes the ability of reactive oxygen species to steal electrons from cell membrane lipids, leading to oxidative injury and to a specialized form of iron-dependent programmed cell death, known as ferroptosis. 18,19 Ferroptosis is a common form of cell demise and has been implicated in the progression of heart failure [20][21][22][23][24][25] and chronic kidney disease [26][27][28] across a broad range of disease aetiologies. The serum level of malondialdehyde (reflecting lipid peroxidation) is used as a biomarker of ferroptosis 29 and is notably elevated and has prognostic significance in patients with cardiomyopathy or declining kidney function.…”
Section: Ferroptosis and The Progression Of Heart Failure And Chronic...mentioning
confidence: 99%